The Association Between the Infection Prevention and Control (IPC) Committee's Performance and Compliance With the Use of Personal Protective Equipment (PPE) in Sembiring Hospital - Alprindo Sembiring Meliala; Efrata Efrata; Friska Ernita Sitorus; Hariati Hariati; Rostiodertina Girsang; Zuliawati Zuliawati; Jekson Martiar Siahaan (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Hospitals play a critical role in preventing nosocomial infections, and the use of personal protective equipment (PPE) is a key strategy for protecting healthcare workers and preventing pathogen transmission. This cross-sectional quantitative study aimed to assess the influence of the Infection Prevention and Control (IPC) Committee's performance on PPE compliance at Sembiring Hospital. A total of 57 healthcare workers participated and were surveyed using structured questionnaires. Data were analysed using univariate, bivariate (Chi-square) and multivariate (logistic regression) methods. All IPC performance indicators, surveillance, supervision, policy and procedure development, training, education effectiveness, participation and collaboration, and PPE availability, were significantly associated with PPE compliance. Multivariate analysis showed that education effectiveness had a significant effect on compliance (p = 0.002; Exp(B) = 16.655; 95% CI: 2.707?90.543). These findings suggest that strengthening the IPC Committee's role in delivering effective education is essential to improve PPE compliance among healthcare workers. For policy and practice, hospitals should prioritise continuous IPC training programmes and institutionalise periodic competency assessments to enhance adherence to PPE protocols and safeguard both staff and patients Keywords: IPC Committee, PPE Compliance, Infection Prevention, Hospital Policy